Perbedaan Hitung Jumlah Trombosit Menggunakan Darah Vena dan Darah Kapiler - Hieronymus Rayi Prasetya (LPPM STIKES Guna Bangsa Yogyakarta, 2016)
Background: Platelets play a role in hemostasis which is the body's mechanisms to prevent and stop the bleeding. Platelets participate in the effort to close the wound, so that the body does not experience a loss of blood and protected from foreign cells. Examination of the platelet count is very important in the diagnosis of diseases, one of which is the diagnosis of dengue hemorrhagic fever (DHF). Examination of blood counts, especially platelets in clinical laboratories causes blood samples in use are not always the venous blood but could use capillary blood. Capillary blood samples are used primarily in pediatric patients, because the venous blood sampling is difficult, patient loads, and also shorten the time when taking blood. The purpose of this study was to determine whether there is a difference in counting the number of platelets using samples of blood veins and capillaries.